Systematic Literature Review: Upaya Peningkatan Kemampuan Berpikir Kritis dalam Pembelajaran Matematika melalui Model Problem Posing pada Peserta Didik - ummi hani; Siti Syifa Mardhotillah; Dwi Susiana Rusmawati; Nani Kurniati (Yayasan Arfah Bin Haji Muhammad Saleh, 2026)
Critical thinking skills are an important aspect of mathematics learning, which can be improved through a variety of learning approaches. This study aims to analyze the relationship between efforts to improve critical thinking skills and the application of problem posing in mathematics learning. The method used is Systematic Literature Review by analyzing 15 research articles published in the 2018–2025 range and obtained through Google Scholar. The articles analyzed include elementary, junior high, high school, and equivalent education levels. Data were collected by examining research articles that discussed the impact of problem posing on mathematical critical thinking skills. The results of the analysis show that problem posing contributes significantly to improving students' critical thinking skills in mathematics learning.